Untethered wavelength-selective multi-shape programmable hybrid soft robot - Eungyoul Oh; Yeonjae Lee; Hyo-Jeong Lee; Youngjin Na; Albert Kim; Jun Dong Park; ChangKyu Yoon; Seung Hyun Song (Scientific Reports)
Abstract Untethered stimuli-responsive soft robotics is a promising field with potential applications in healthcare, automation, and human-robot interaction. However, current limitations restrict many soft robots to binary shape actuation, limiting their functionality to a single mechanical task. In this study, we introduce an untethered wavelength-selective multi-shape programmable soft robot using silicone/hydrogel materials. By leveraging metal nanoparticle-embedded silicone elastomer, our robot achieves reversible shape transformations in response to specific light wavelengths. We also engineered multiple distinct stiffness in key components like hinges and panels, enabling origami-like folding actuation. Our fabricated robot demonstrates four distinct shape morphologies controlled by two light wavelengths. This innovative combination of materials and selective actuation mechanism lays a strong foundation for advanced soft robotic systems capable of diverse mechanical tasks.